Analysis of end-winding proximity losses in a high-speed PM machine - Mlot Adrian; Lukaniszyn Marian; Korkosz Mariusz (Archives of Electrical Engineering, 2016)
This paper presents a finite element investigation into the proximity losses in a high-speed permanent magnet (PM) machine for traction applications. A three-dimensional (3D) finite element analysis (FEA) is employed to evaluate and identify the endwinding contribution into the overall winding power loss generated. The study is focused on the end-winding effects that have not been widely reported in the literature. The calculated results confirm that the end-winding copper loss can significantly affect the eddycurrent loss within copper and it should be taken into account to provide reasonable prediction of total losses. Several structures of the end-winding are analyzed and compared in respect to the loss and AC resistance. The results clearly demonstrate that the size of the end-winding has a significant impact on the power loss. The calculated results are validated experimentally on the high-speed permanent magnet synchronous machine (PMSM) prototype for selected various winding arrangements.